2022
DOI: 10.1101/2022.06.21.497077
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibodies to protozoan variable surface antigens induce antigenic variation

Abstract: The genomes of most protozoa encode families of variant surface antigens, whose mutually exclusive changes in expression allow parasitic microorganisms to evade the host immune response1,2. It is widely assumed that antigenic variation in protozoan parasites is accomplished by the spontaneous appearance within the population of cells expressing antigenic variants that escape antibody-mediated cytotoxicity1,2. Here we show, both in vitro and in animal infections, that antibodies to Variant-specific Surface Prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…The anchor might also be involved in signal transduction. For instance, the addition of homologous antibodies to living paramecia induces serotype switches [22] and this was also reported recently for several other organisms, e.g., Giardia, Trypanosoma, and the ciliate Tetrahymena [23]. Furthermore, the GPI-anchored folate receptor on the Paramecium surface was shown to confer a folate-specific chemoresponse [24]; thus, GPI-mediated signal transduction appears to exist in Paramecium.…”
Section: Introductionsupporting
confidence: 69%
“…The anchor might also be involved in signal transduction. For instance, the addition of homologous antibodies to living paramecia induces serotype switches [22] and this was also reported recently for several other organisms, e.g., Giardia, Trypanosoma, and the ciliate Tetrahymena [23]. Furthermore, the GPI-anchored folate receptor on the Paramecium surface was shown to confer a folate-specific chemoresponse [24]; thus, GPI-mediated signal transduction appears to exist in Paramecium.…”
Section: Introductionsupporting
confidence: 69%
“…The relatively "protected" tissue spaces may serve as a site for this iterative process to occur. Another intriguing possibility is that partial immune evasion is advantageous for the parasite: a recent study suggested that exposure to sublethal antibody concentrations can trigger a VSG switch in T. brucei 30 . Perhaps parasites expressing these partially evasive variants are more prone to switching to a completely new VSG.…”
Section: Discussionmentioning
confidence: 99%
“…To identify differentially expressed genes (DEGs) that might be related to the process of antigenic variation triggered by antibodies, biological replicates of clone1 were incubated for 4 h with low concentrations of mAb 7C2 to induce VSP switching and RNA sequencing was performed [60]. Surprisingly, only 7 DEGs (FDR < 0.05) were found between trophozoites before and after treatment (Table S12).…”
Section: Transcriptomic and Proteomic Analyzesmentioning
confidence: 99%